Gender inequality and restrictive gender norms: framing the challenges to health. Issue 10189 (15th June 2019) - Heise, Lori; Greene, Margaret E; Opper, Neisha; Stavropoulou, Maria; Harper, Caroline; Nascimento, Marcos; Zewdie, Debrework
Summary: Gender is not accurately captured by the traditional male and female dichotomy of sex. Instead, it is a complex social system that structures the life experience of all human beings. This paper, the first in a Series of five papers, investigates the relationships between gender inequality, restrictive gender norms, and health and wellbeing. Building upon past work, we offer a consolidated conceptual framework that shows how individuals born biologically male or female develop into gendered beings, and how sexism and patriarchy intersect with other forms of discrimination, such as racism, classism, and homophobia, to structure pathways to poor health. We discuss the ample evidence showing the far-reaching consequences of these pathways, including how gender inequality and restrictive gender norms impact health through differential exposures, health-related behaviours and access to care, as well as how gender-biased health research and health-care systems reinforce and reproduce gender inequalities, with serious implications for health. The cumulative consequences of structured disadvantage, mediated through discriminatory laws, policies, and institutions, as well as diet, stress, substance use, and environmental toxins, have triggered important discussions about the role of social injustice in the creation and maintenance of health inequities, especially along racial and socioeconomic lines. This Series paper raises the parallel question of whether discrimination based on gender likewise becomes embodied, with negative consequences for health. For decades, advocates have worked to eliminate gender discrimination in global health, with only modest success. A new plan and new political commitment are needed if these global health aspirations and the wider Sustainable Development Goals of the UN are to be achieved.